Seismic sliding stability analysis of reinforced soil retaining walls. Issue 6 (23rd September 2019) - Xu, P.; Hatami, K.; Jiang, G.
Abstract : The Coulomb linear slip plane is adopted in most of the current design guidelines for reinforced soils walls based on the assumption that the reinforced zone acts as a rigid body. However, among major shortcomings of the Coulomb linear slip plane assumption is that its geometry is not consistent with the two-part wedge failure geometry that is typically observed in many model tests and numerical simulations, and the influence of reinforcement design on the sliding stability of reinforced mass cannot be included in the analysis. In this paper, a kinematic limit analysis method is developed for sliding stability calculations of reinforced soil retaining walls subjected to ground acceleration, which is based on the more commonly-observed, two-part wedge failure mechanism. The proposed analysis method is validated against the results of two shaking table model tests. It is subsequently used to investigate the influence of reinforcement and backfill properties, as well as those of vertical acceleration and wall height, on the predicted sliding yield acceleration and failure plane inclination angle in the reinforced zone of the reinforced soil retaining wall systems.